Evaluation of Thawing Curves of Beef Strip Loin Steaks Using Various Thawing Methods - Lauren M. Frink; Lindsey K. Decker; Erin S. Beyer; Michael D. Chao; Morgan D. Zumbaugh; Jessie L. Vipham; Travis G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2024)
Objective:The objective of this study was to evaluate and determine thaw rate and time of strip steaks thawed using methods that are recommended by the U.S. Department of Agriculture and those commonly used by consumers. Study Description:Strip steaks collected from a beef packing facility were randomly assigned a thaw method. Initially, steaks were vacuum packaged and then frozen at -40°F until thawed. Two thawing methods were USDA-approved: thawing in a refrigerator (REF) and in cold water (CW); while the other two methods evaluated are commonly used by consumers: thawing on the countertop (CT) and in hot water (HW). The thawing temperatures were: REF at 35.6–37.4°F in the refrigerator; CW maintained at 35.6–37.4°F in water; CT at 68°F; and HW at 104°F. Temperatures of the steaks were recorded every 30 minutes for CW and REF, every 10 minutes for CT, and every thirty seconds for HW to determine the thaw time and rate. Results:Thawing time differed (P<0.05) among treatments in this study (HWP<0.05) among treatments with a similar trend (HWP<0.05) from REF until 5 hours prior to thaw point, at which point the temperatures were similar (P>0.05) for the remaining thawing period. Moreover, REF steaks were warmer (P<0.05) than CW steaks from 13 to 5 hours prior to thaw point. In the final 5 hours, CW and REF steaks were similar (P>0.05) in temperature. Furthermore, among all treatments, CT steaks were the coldest(P<0.05) from 5 to 2 hours prior to thaw point. However, in the final 2 hours, CT steaks were at similar (P>0.05) temperatures as CW and REF. Due to the short period of thawing time and the observed rapid thawing rate, HW samples were the coldest (P<0.05) in the final 10 minutes prior to thaw point. The Bottom Line:Of the four thaw methods utilized in this study, the safest methods are those approved by the USDA (CW and REF). Thawing meat on the countertop or in hot water may be efficient and convenient methods for consumers, but it is important to take the extra time to thaw meat properly for safety.
Keywords: thawing time; thawing rate; temperature; beef